The ER Lumenal Hsp70 Protein FpLhs1 Is Important for Conidiation and Plant Infection in Fusarium pseudograminearum - Chen, Linlin; Geng, Xuejing; Ma, Yuming; Zhao, Jingya; Chen, Wenbo; Xing, Xiaoping; Shi, Yan; Sun, Bingjian; Li, Honglian (Frontiers in Microbiology, 2019)
Hsp70s (heat shock protein 70s) are a class of molecular chaperones that are highly conserved and ubiquitous in organisms ranging from microorganisms to plants and humans. Hsp70s play key roles in cellular development and protecting living organisms from environmental stresses such as heat, drought, salinity, acidity, and cold. However, their functions in pathogenic fungi are largely unknown. Here, a total of 14 FpHsp70 genes were identified in Fusarium pseudograminearum, including 3 in the mitochondria, 7 in the cytoplasm, 2 in the endoplasmic reticulum (ER), 1 in the nucleus, and 1 in the plastid. However，the exon–intron boundaries and protein motifs of the FpHsp70 have no consistency in the same subfamily. Expression analysis revealed that most FpHsp70 genes were up-regulated during infection, implying that FpHsp70 genes may play important roles in F. pseudograminearum pathogenicity. Furthermore, knockout of an ER lumenal Hsp70 homologue FpLhs1 gene reduced growth, conidiation and pathogenicity in F. pseudograminearum. These mutants also showed a defect in secretion of some proteins. Together, FpHsp70s might play essential roles in F. pseudograminearum and FpLhs1 is likely to act on the development and virulence by regulating protein secretion.